Dialogue of Heart: Interreligious Dialogue through Rumi’s Poetry - Mochammad Maola (Ulumuna, 2018)
Living in harmony is required in a society which is characterized by cultural and religious diversity. It requires dialogue skills in various aspects of life during the day for allowing a sense of appreciation among humans and can be embedded within each other. Interreligious dialogue is a part of the disciplines covered in the field of religious studies. Indeed, the approach of interreligious studies is among the alternative mechanism in dealing with defamation of conflict between Islam and non-Islamic religions. This case needs to be dived so that alternative approaches are scattered in applying the dialogue between religions. Rumi (Mewlana Jalaluddin Rumi) is a famous name of Muslim mystics and great Sufi scholar with many adherents. He has written many books, especially in poetry. The way Rumi universally see religion and humankind through his poetry is exciting to be understood as a dialogue of heart. In order to reasoning, this paper will use the help of reading by Swidler and Pruitt. This paper uses literature review toward Rumi’s book entitled Mathnawī. From the findings and discussion, it can be concluded that mysticism introduced interreligious dialogue through poetry, and put heart or soul as the tool to perform interreligious dialogue.